Immune response of bos indicus cattle against the anti-tick antigen Bm91 derived from local rhipicephalus (Boophilus) microplus ticks and its effect on tick reproduction under natural infestation - Lambertz C. (2017)
Antigens of anti-tick vaccines are more efficacious for homologous challenge with local tick strains. cDNA clones encoding for Bm91 from local Rhipicephalus (Boophilus) microplus strains were developed to immunize Bos indicus cattle under field conditions. Three groups of six animals each were injected with the antigen Bm91, saline, and adjuvant, respectively. Animals were immunized three times at 3-week intervals and a fourth time after six months. The anti-Bm91 antibody level, measured by ELISA, was monitored for 7 months and the reproductive performance of naturally infested R. (B.) microplus was determined. Bm91-immunized animals developed a strong immune response expressed by high anti-Bm91 levels remaining on high levels until the end of the study. Western blot analysis confirmed that Bm91 is immunogenic. Compared to control animals, the reproductive efficiency index and the egg viability were 6% and 8%, respectively, lower in the Bm91 group (P < 0.05). In conclusion, it was demonstrated that Bm91 induced a long-lasting immune response. However, the effect on the tick reproduction was not sufficient for an efficient tick control. Further studies under field conditions are warranted to enhance the effect on the tick reproduction by optimizing the immunization regimen, alone or in combination with other vaccine candidate antigens. © 2012 Christian Lambertz et al.